Strong sexual selection despite spatial constraints on extrapair paternity. (14th February 2020) - Cramer, Emily R A; Greig, Emma I; Kaiser, Sara A
Abstract: Extrapair paternity should contribute to sexual selection by increasing the number of potential mates available to each individual. Potential copulation partners are, however, limited by their proximity. Spatial constraints may therefore reduce the impact of extrapair paternity on sexual selection. We tested the effect of spatial constraints on sexual selection by simulating extrapair copulations for 15 species of socially monogamous songbirds with varying rates of extrapair paternity. We compared four metrics of sexual selection between simulated populations without spatial constraints and populations where extrapair copulations were restricted to first- and second-order neighbors. Counter to predictions, sexual selection as measured by the Bateman gradient (the association between the number of copulation partners and offspring produced) increased under spatial constraints. In these conditions, repeated extrapair copulations between the same individuals led to more offspring per copulation partner. In contrast, spatial constraints did somewhat reduce sexual selection—as measured by the opportunity for selection, s' max, and the selection gradient on male quality—when the association between simulated male quality scores and copulation success (e.g., female preferences or male–male competition) was strong. Sexual selection remained strong overall in those populations even under spatial constraints. Spatial constraints did not substantially reduce sexual selection when the association between male quality and copulation success was moderate or weak. Thus, spatial constraints on extrapair copulations are insufficient to explain the absence of strong selection on male traits in many species. Abstract : Copulations outside the pair bond often occur only within local neighborhoods, thus preventing a single male from monopolizing all extrapair paternity opportunities in a population. It has been proposed that such spatial constraints would limit sexual selection. Our simulations show that sexual selection, though reduced, can remain strong despite spatial constraints on extrapair paternity.